The unintentional effects of the Conditional Cash Transfers Programs on agriculture: evidence from Peruvian farming households - Del Pozo Loayza, César Edinho (2016)
This paper examines the unintentional effects of Programa Juntos (a Conditional Cash Transfer Program in Peru) on agriculture outcomes using data from household surveys, and a Differences-in-Differences estimator. I found evidence of potential negative effects of program on agriculture; particularly the evidence suggests that program reduces the value of agricultural production and the hectares of land used; these results are opposite to previous empirical evidence for the Latin American context. To explore some causal chains, I estimate the effects of program on labor supply; I found that the program can generates a disincentive effect on adult labor supply for agriculture.